A Web Information System to Improve the Digital Library Service Quality - Cabrerizo, Francisco Javier; Martínez, Mª Ángeles; López-Gijón, J.; Chiclana, Francisco; Herrera-Viedma, Enrique (Frontiers in Artificial Intelligence and Applications, 2020)
To asses the quality of the services provided by a digital library, traditional measures, such as the size of its collection, have usually been utilized. However, service quality also has to be evaluated by considering users' expectations. In addition, as a digital library plays an important role in the educational progress of a society, it is very important not only to measure the quality of its services but also to improve them. In this contribution, we present a web information system which supports the staff of a digital library to carry out decisions with the aim of improving the services offered by it. To do so, this system provides some advice taking into account both objective criteria, related to quantitative data, and subjective criteria, related to users' judgments.
Ponencia de la conferencia "nternational Conference on System Science and Engineering, ICSSE 2015; Morioka; Japan; 6 July 2015 through 8 July 2015"
Keywords: digital libraries; LibQUAL+; web; Scopus(2)